(untitled) (Modern Problems of Metallurgy, 2021)
Low energy efficiency of foundry class electric arc steelmaking furnaces (EAF) mainly is caused by heat loss by massive lining during forced downtime. A low-power transformer doesn’t allow, in the conditions of classical technology, practice of traditional water-cooled elements in order to replace partially the lining, what determines increased refractory consumption. The aim is energy and refractory savings. On the basis of numerical modeling of heat exchange by radiation in the EAF working space, taking into account capacity, bath shape factor, duration of technological period of heat, a multiple regression equation for power of heat loss with cooling water was obtained. Three-row water-cooled wall panels with a spatial structure are elaborated, which provide a decrease in heat loss by 14 %, in comparison with two-row ones. Estimates of optimal relative cooled surface of the EAF working space, providing refractory savings up to 25-30%, are substantiated.